Circular Economy in EU 27 Agribusiness. Operational Factors of Integrability - Antal, Sándor; Vincze, Judit (Acta Carolus Robertus, 2024)
Recent global events are increasingly highlighting the need to review and renew the current social and economic system of the European Union. Although the economic crisis of 2008 was followed by a significant boom, the way out of the shock caused by the social, political and economic events of the 2020s is not yet in sight. Despite the fact that the European Union has the strategic goals necessary for this, the development and implementation of tactical and operational plans still await. However, this delay - according to empirical experience - causes serious disturbances and damages both in agriculture and in the entire value chains based on agricultural production, in agribusiness. In relation to the change in social and economic policy approach and renewal, the question arises as to how ready the EU - as a community - is to eliminate the linear economic model and to adapt the circular economy to agribusiness. Another important dilemma is the extent to which the member countries that joined in 2004 managed to catch up, which is a basic condition for the integration of the circular economic model into agribusiness. Taking into account the role of agribusiness in the community of the European Union, as well as the set economic goals of the community, the connection of the circular economic model and agribusiness, which fundamentally determines national economies, and the acceleration of this process cannot be postponed any longer. In connection with the above, our study explores the fundamental factors that, as indicators, indicate the preparedness and shortcomings of the European Union in the field of implementing the circular economy. At the macro- and micro-economic level, we analyzed the components whose development either indirectly or directly affects agribusiness. Within this, we examined the evolution of emissions, energy consumption, waste production, and the correlations between them. With reference to agribusiness, we examined the results of agricultural production, the situation of food processing, and the development of the food foreign trade balance. Based on our results, a European Union with a different economic system with respect to the member countries is revealed. In this heterogeneous economic environment, the transition of agribusiness to a circular economy raises countless questions. The first dilemma that arises is whether it is possible to approach the success and progress of this process with GDP as an output-based indicator in the aspect of the economic spatial structure of the European Union.